2013
DOI: 10.1016/j.jvs.2012.10.112
|View full text |Cite
|
Sign up to set email alerts
|

Results of elective and emergency endovascular repairs of popliteal artery aneurysms

Abstract: These results support elective EVPAR in anatomically suitable patients with increased risk for open repair; however, major adverse events after EVPAR, mainly after emergency repairs, are frequent. A prospective randomized multicenter study to justify EVPAR in the emergent setting is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 27 publications
1
47
0
6
Order By: Relevance
“…There was no significant difference in primary patency for EVPAR compared with surgical repair, with a pooled HR of 1.30 (95% CI 0.79 to 12.14, p=0.189; Figure 2B). 14,15,18,21,24 A sensitivity analysis comparing primary patency in studies using both Hemobahn and Viabahn stent-grafts 14,20,21,23,25,26 compared to studies reporting Viabahn stent-grafts only [15][16][17][18][19]22,24,27 showed no significant difference in primary patency ( Figure 2C). …”
Section: Primary Outcomesmentioning
confidence: 99%
“…There was no significant difference in primary patency for EVPAR compared with surgical repair, with a pooled HR of 1.30 (95% CI 0.79 to 12.14, p=0.189; Figure 2B). 14,15,18,21,24 A sensitivity analysis comparing primary patency in studies using both Hemobahn and Viabahn stent-grafts 14,20,21,23,25,26 compared to studies reporting Viabahn stent-grafts only [15][16][17][18][19]22,24,27 showed no significant difference in primary patency ( Figure 2C). …”
Section: Primary Outcomesmentioning
confidence: 99%
“…8,[28][29][30] All of the endovascular cases were elective, but some studies have shown that this technique can also be used in urgent/emergency situations, with primary patency reaching 69%, and secondary patency of up to 91%, offering a less invasive option for patients at high risk from surgery, even in acute situations. 31 Studies report primary patency of 86% to 95% and secondary patency of 96.90% to 100% for aneurysms repaired with elective endovascular surgery. [31][32][33][34] Cases repaired with great saphenous vein grafts by conventional surgery have patency of 78.80% to 87.50% in the first year, with limb salvage rates of 94.30%.…”
Section: Discussionmentioning
confidence: 99%
“…31 Studies report primary patency of 86% to 95% and secondary patency of 96.90% to 100% for aneurysms repaired with elective endovascular surgery. [31][32][33][34] Cases repaired with great saphenous vein grafts by conventional surgery have patency of 78.80% to 87.50% in the first year, with limb salvage rates of 94.30%. 20,26 Our patient sample was comparable with previous studies, with stent patency of 80% during the first year and limb survival of 100% over the first 90 days after ES, while cases treated with OS had 95.23% patency in the first month and 75% after 1 year, and a 90-day limb survival rate of 95.23%, including emergency cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several procedures are described in the literature, such as excision, ligation, and bypass grafting with an autologous vein or prosthetic material. Nowadays, endovascular repair is also feasible and safe [4], but we ruled it out mainly due to the extension of the hematoma that had to be evacuated and the size of the aneurysm. Thrombocytopenia is a common side effect of azacitidine; our patient’s pre-operative platelet count was 17,000 platelets/μL.…”
Section: Discussionmentioning
confidence: 99%